Hypoxia inducible factor HIF-1 promotes myeloid-derived suppressor cells accumulation through ENTPD2/CD39L1 in hepatocellular carcinoma - Chiu, David Kung-Chun; Tse, Aki Pui-Wah; Xu, Iris Ming-Jing; Di Cui, Jane; Lai, Robin Kit-Ho; Li, Lynna Lan; Koh, Hui-Yu; Tsang, Felice Ho-Ching; Wei, Larry Lai; Wong, Chun-Ming; Ng, Irene Oi-Lin; Wong, Carmen Chak-Lui (Nature communications, 2017)
Myeloid-derived suppressor cells (MDSCs) possess immunosuppressive activities, which allow cancers to escape immune surveillance and become non-responsive to immune checkpoints blockade. Here we report hypoxia as a cause of MDSC accumulation. Using hepatocellular carcinoma (HCC) as a cancer model, we show that hypoxia, through stabilization of hypoxia-inducible factor-1 (HIF-1), induces ectoenzyme, ectonucleoside triphosphate diphosphohydrolase 2 (ENTPD2/CD39L1), in cancer cells, causing its overexpression in HCC clinical specimens. Overexpression of ENTPD2 is found as a poor prognostic indicator for HCC. Mechanistically, we demonstrate that ENTPD2 converts extracellular ATP to 5′-AMP, which prevents the differentiation of MDSCs and therefore promotes the maintenance of MDSCs. We further find that ENTPD2 inhibition is able to mitigate cancer growth and enhance the efficiency and efficacy of immune checkpoint inhibitors. Our data suggest that ENTPD2 may be a good prognostic marker and therapeutic target for cancer patients, especially those receiving immune therapy. Myeloid-derived suppressor cells (MDSCs) promote tumor immune escape. Here, the authors show that in hepatocellular carcinoma, hypoxia induces the expression of ENTPD2 on cancer cells leading to elevated extracellular 5′-AMP, which in turn promote the maintenance of MDSCs by preventing their differentiation.